3(2n+2)=8(6n+1)+4

Simple and best practice solution for 3(2n+2)=8(6n+1)+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2n+2)=8(6n+1)+4 equation:



3(2n+2)=8(6n+1)+4
We move all terms to the left:
3(2n+2)-(8(6n+1)+4)=0
We multiply parentheses
6n-(8(6n+1)+4)+6=0
We calculate terms in parentheses: -(8(6n+1)+4), so:
8(6n+1)+4
We multiply parentheses
48n+8+4
We add all the numbers together, and all the variables
48n+12
Back to the equation:
-(48n+12)
We get rid of parentheses
6n-48n-12+6=0
We add all the numbers together, and all the variables
-42n-6=0
We move all terms containing n to the left, all other terms to the right
-42n=6
n=6/-42
n=-1/7

See similar equations:

| 14w=-56 | | 48-(-42x-30)=252x+228 | | 7(2+2x)+(x+2)*6=0 | | X+10y=307 | | 6-4/4-x=3/5 | | 1/5(-20k+75)=5+10k | | 17z+33=6z | | 4g+(6+2g)*3=0 | | 3x-7=4-2(3x-4) | | (2)/(x)+3=(4)/(5x)+(31)/(10) | | 1/5+1/4+v=7/60 | | 2×+y=60 | | (3n+6)*3+(2n+2)*4=0 | | 0.2(x-20)=4 | | 3a=5a-20 | | 48-(-63x-30)=252x+228 | | -(3x-5)+x=-5x+1+x | | x^2-7x+11=5 | | X/3-x/4=7/2 | | 6n-12=-8+3n-8 | | 1+8b=-15+6b | | 6n-12=3n-16 | | 15x-13+7x+19=180 | | 15=6-2x | | 4(x+1)-2x=5x-8 | | -15×=84-8x | | 4(3x+2)-7=0 | | 5x+x=10+x | | (2x+3)(x)=280 | | 5x+x=10x | | 2(1/7x)+2x=160 | | 4x-6=94 |

Equations solver categories